Importancia del “efecto rebote” o paradoja de Jevons en el diseño de la política ambiental (2015)
This reflective article considers the design of environmental policies in Colombia, which has focused on the use of natural resources as pool of materialsand energy to generate economic growth. In this sense, it becomes clear thatcollective concern for environmental supply management as cornerstone for sustainable development established in the political constitution, has failed mainly by the reagent and coercive approach to policies and regulations coupled with little promotion for the transformation of national consumer life style, this has generated a rebound effect increasing use and consumption of natural resources (especially non-renewable) limiting energy efficiency; for example, this can be seen in the national mining and energy sector. Whereas there is a global concern for sustainability, it is necessary that the design of national environmental policies away from the economic and technological optimism of the current economic model and certainly incorporate in their political the strategies that balance the relationships between supply and demand of environmental services that support national development, while encouraging the responsible consumption in the Colombian population, in addition to include the community initiatives on regulation and social inclusion in the management of environmental godos and services to generate strong sustainability processes.